EFFECTS OF FORMATIVE ASSESSMENT IN MATHEMATICS EDUCATION - (:unkn) unknown (INT GRP PSYCHOL MATH EDUC, 2011)
The purpose of the research in this paper is to evaluate the effectiveness of formative assessment on student achievement. For an experiment, an intervention was designed that involves eight degree students of a randomly chosen middle school located in Istanbul. 27 students, 14 of which are the experimental group and the rest is the control, took parts as the subjects and pre-test, post-test with control group was used as the experimental model. Maths and retention tests were conducted in the end to draw the conclusion and statistical analysis of the results of those have shown that formative assessment is positively influential on math achievements as well as memorizing capabilities of students.
Keywords: FEEDBACK